Combined strength exercises on dry land and in the water to improve swimming parameters of athletes with paraplegia - Skucas, K.; Pokvytyte, V. (The Journal of Sports Medicine and Physical Fitness, 2018)
BACKGROUND: The aim of the present research was to examine the effects of 12 weeks of combined dry land strength and resistance swimming training for increasing upper body strength, swimming performance and stroking parameters in swimmers with paraplegia and to determine correlation between these parameters.